ANALISIS PELAKSANAAN PROGRAM GERAKAN LITERASI SEKOLAH (GLS) DI SDN 1 GITGIT DALAM MENUMBUHKAN BUDAYA MEMBACA PADA ANAK - I Gede Arya Wiradnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Research on the analysis of the implementation of the school literacy program in SDN 1Gitgit aims to describe: (1) implementation of the school literacy program in relation to thegrowth of reading culture, (2) obstacles to the implementation of the school literacy program,(3) efforts to address the obstacles of the school literacy program. This research is a qualitativedescriptive study. Data were collected by interview and observation. Data analysis was done byqualitative descriptive method. The results of research on the implementation of the school literacyprogram at SDN 1 Gitgit shows that: (1) the implementation of school literacy program is stillat the stage of familirization and has not been able to foster a reading culture in students; (2)obstacles to the implementation of the school literacy program program are: (a) lack of knowledgeof school management; (b) lack of teacher exemplary; (c) low awareness of students to returnbooks; (d) inadequate funding of school literacy activities; and (e) lack of focus of students incarrying out the reading activity 15 minutes. The effort to handle the obstacles of the schoolliteracy program is done by: (a) developing the program in a sustainable manner and involvingall school members; (b) optimize library management in schools and facilities in it, and (c)provide guidance to students to return the book in its place after 15 minutes of reading a book inthe library